REPRESENTASI DAN PARTISIPASI KELAS MENENGAH DALAM PROGRAM KELUARGA BERENCANA PRIA (Studi Kasus di Kecamatan Dlingo Kabupaten Bantul) - , VIBRIZA JULISWARA, Derajad S. Widhyarto, S.Sos., M.Si ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Behind the government's success in limiting the birth of this country there is still a negative impact is felt community, especially among women. Responsibility to form a prosperous family affairs including limiting the number of children, not just on the shoulders of his wife.This study will analyze the factors that led to increased community participation in the District Dlingo Bantul. The actor who became an agent of change is the middle class.Representation of the middle class has a significant influence on increasing the number of family planning acceptors Men. Reason KB opted for economic demands with children amounted to three to four people feel burdensome. The high cost of living and education for their children's awareness has led them to not increase the number of children. In addition, their wives are feeling tired because of the emergence of unfavorable effects of contraception they used. Circle KB Men Men Mulyo in District Dlingo until recently there were 85 active acceptors, they are interesting in KB the man after being given the explanation that the vasectomy is not the same as the castrated and no negative effects on the health of their bodies.Achievement of male family planning acceptors in the district is still dominated by middle-class society. The image is a representation, a "resurrection" is understood as a "lived experience". In this sense, how to construct the image of the collective image of the individual. to submit to the collective image.This can be seen in the case of how a man of family planning acceptors were chosen to be the identity of the middle class.gender awareness in recognition of women's reproductive rights was regarded as a representation of one of the middle class. To serve the wants and needs of men who will undergo a MOP, the Government in addition to technical factors must also pay attention to cultural to social factors that need to be synergy between the three factors for success and increase the participation of males in the MOP program predisposing factors (age, educational level, the level of knowledge, attitudes, perception, social and cultural values), enabling factors (access to family planning service men) and reinforcing factors (of wife, friend attitudes, practices friends).